Lessons Learned from Mainstreaming HIV/AIDS in Transport Sector Projects in Sub-Saharan Africa - World Bank (Washington, DC, 2012)
The Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) pandemic burdens Sub-Saharan Africa (SSA) and continues to constrain its social and economic advancement. Joint United Nations Program on HIV/AIDS (UNAIDS) has estimated that in southern Africa alone, 930,000 adults and children died of AIDS in 2005. This represents about one-third of AIDS deaths recorded globally that year. In addition, about 12 million children below the age of 17 in SSA are estimated to have lost one or both parents to AIDS. Africa Technical Transport Sector Unit (AFTTR) has made progress in mainstreaming HIV/AIDS in its portfolio. However, there is still more work ahead in ensuring that all projects are mainstreamed as needed. In this context, the transport sector board needs to continue supporting such future mainstreaming efforts by establishing a sector board strategy for HIV/AIDS activities on Bank-financed transport projects. The diverse nature of transportation activities implies that mainstreaming is both challenging and urgent. In 2000, the Africa transport team gave high priority to its contribution to the campaign against the HIV/AIDS pandemic and pledged to mainstream HIV/AIDS actions in the Bank's lending operations and at country level in the transport sector. The transport sector contributed significantly through integrating simple activities into its operations (such as HIV/AIDS contract clauses into bidding documents for road construction site workers). Similarly, the Bank financed a first-round workshop to prepare HIV/AIDS prevention policy in the workplace for Ministry employees. Its main objective is to develop and implement highly focused prevention interventions to reduce HIV/AIDS prevalence and slow down the spread of the disease in the transport sector. This document is subdivided in four sections. The first section gives background information on the transport sector and HIV/AIDS. The second section describes the Bank's transport sector activities, with particular focus on the Africa region and its achievements regarding HIV/AIDS. The third section presents the process and the results of the assessment of the Africa transport sector portfolio for HIV/AIDS mainstreaming. The fourth section enumerates the lessons learned as well as the recommendations made to the World Bank's Transport Sector Board and to stakeholders in the client countries.